Possibilities of Electron Beam Melting Technology: Titanium Processing - Fousova, Michaela; Vojtech, Dalibor (Manufacturing Technology Journal, 2018)
Nowadays, 3D printing of metallic materials is a hot topic in many industrial spheres as it provides a one-step production of very complex parts. The additive principle based on processing of powders or wires in many successive layers minimizes material losses and so production costs. It also ensures great control over built shapes exactly according to computer-designed models. The most available technology is Selective Laser Melting (SLM) that uses a laser beam to selectively melt a metallic powder into the form of a desired product. The Electron Beam Melting (EBM) technology, that is based on a similar principle, is not so widespread, especially in the Czech Republic. Instead of a laser beam, it uses an electron beam. Related to that, EBM is far more energy-efficient and has different process characteristics. In this contribution, on the example of titanium alloy, we show marginal possibilities of this technology in the processing of bulk materials, from porous to highly dense.
Keywords: EBM; electron beam melting; Ti6Al4V; mechanical properties